2007
DOI: 10.1016/j.cognition.2006.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of age-of-acquisition for concrete nouns and action verbs: Evidence for partly distinct representations?

Abstract: There is growing evidence that words that are acquired early in life are processed faster and more accurately than words acquired later, even by adults. As neuropsychological and neuroimaging studies have implicated different brain networks in the processing of action verbs and concrete nouns, the present study was aimed at contrasting reaction times to early and later-acquired action verbs and concrete nouns, in order to determine whether effects of word learning age express differently for the two types of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
(60 reference statements)
5
16
2
Order By: Relevance
“…naming can merely reflect the lack of power in this analysis, our results fully replicated those of Boulenger, Décoppet, Roy, Paulignan, and Nazir (2008), in a study on normal participants, involving similar stimuli (actions and concrete objects), the same task (naming), but a much larger number of observations than in our study. Double dissociations together with the differential AoA effect for tool nouns and action verbs suggest that their relatedness with identical action contents is not sufficient-or does not constitute the only principle-for determining their organization in the brain.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…naming can merely reflect the lack of power in this analysis, our results fully replicated those of Boulenger, Décoppet, Roy, Paulignan, and Nazir (2008), in a study on normal participants, involving similar stimuli (actions and concrete objects), the same task (naming), but a much larger number of observations than in our study. Double dissociations together with the differential AoA effect for tool nouns and action verbs suggest that their relatedness with identical action contents is not sufficient-or does not constitute the only principle-for determining their organization in the brain.…”
supporting
confidence: 89%
“…5 The AoA is held to differentially affect words that belong to different classes and are represented within different brain networks (Ghyselinck et al, 2004). Although the lack of correlation between AoA and action 5 Note that AoA can also affect verb retrieval (e.g., Colombo & Burani, 2002;Morrison et al, 2003), depending on the aspects of word processing tapped by a given task (see Boulenger et al, 2008). COGNITIVE NEUROPSYCHOLOGY, 2010, 27 (5) PAPEO ET AL.…”
Section: Nouns and Verbsmentioning
confidence: 97%
“…The findings from these ratings were interesting as the results revealed no significant differences between nouns and verbs on their spoken-word frequency and imageability ratings. This is contrary to findings from English (Bird et al, 2001(Bird et al, , 2003 and French (Boulenger et al, 2007), where verbs obtain significantly lower 8 R.S.W. Alyahya and J. Druks imageability ratings compared to nouns.…”
Section: Druks and Mastersoncontrasting
confidence: 85%
“…The results revealed that nouns (M = 5.06, SD = 0.73) obtained somewhat higher imageability ratings than verbs (M = 4.88, SD = 0.64), but the difference was not significant (t(98.19) = 1.31, p = .191). These results differ from those in other languages, such as English (e.g., Bird, Franklin, & Howard, 2001) and French (e.g., Boulenger, Décoppet, Roy, Paulignan, & Nazir, 2007), where verbs obtain significantly lower imageability rating compared to nouns. Therefore, a new rating data was collected from a different sample of informants in order to confirm the previous results.…”
Section: Imageabilitycontrasting
confidence: 81%
“…Although less common, the opposite pattern–relatively spared abstract word access compared to concrete word access–has also been documented [19][23]. This double dissociation is strong evidence that access to the two word categories is represented in terms of at least a partially dissociable neural representation, a claim which is has been further buttressed by brain imaging evidence [6], [24][28]. Thus, converging evidence from a number of distinct sub-disciplines and methodologies lend support to the hypothesis that abstract and concrete words are in many ways unique, both in terms of their unique lexical-semantic properties and their neural representation.…”
Section: Introductionmentioning
confidence: 97%